DIMENSI GENDER PADA PERTANIAN PADI DI KABUPATEN TOBA SAMOSIR PROVINSI SUMATERA UTARA (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2015)
Rice farm at Toba Samosir Regency has its unique on gender dimension. The people of Toba Samosir Regency was dominated by Bataknese. In Bataknese, the woman farmer as a dominant figure on rice farming. This research aims to analyze gender participation on rice farming and on rice farmers’ households. Harvard Model of analysis is the way to analyze that participation. The result shows the works of rice farming those have been dominated by woman farmer are seeding, planting, weeding, fertilizing, croping. The works of rice farming those have been dominated by man farmer are land clearing and erodication of pests. On rice farmers’ households, the public and domestic role have been dominated by woman. The social role has been dominated by man. The dominant factors that inhibited gender relation are the norms of Bataknese society.